Enhancing student writing motivation through canva-based instruction in hotel accommodation class - Fauziyyah Mufida Suni; Wulandari Ella (Journal of Education, Social & Communication Studies, 2026)
Mastering writing skills is important for vocational school students, yet they are low in motivation due to monotonous learning media. This study measures the potential of Canva as a learning medium to enhance writing motivation among vocational high school students. The research employs a Pretest-Posttest Control-Group Design with 70 students in grade 10 enrolled in hotel accommodation at SMKN 1 Kalasan. Participants were cluster-randomised into a treatment and a control group. Data were collected using pre- and post-test questionnaires. The questionnaire demonstrated strong validity and high reliability. Quantitative data were analysed using descriptive statistics and One-Way Analysis of Covariance (ANCOVA), resulting in significant treatment effects (p < .05) when utilizing Canva. The experiment group's learning with Canva consistently shows higher motivation and engagement. Canva-based instruction effectively enhanced students' writing motivation in a vocational ESP setting. Integrating Canva into English language writing instruction effectively increases students’ motivation to learn. These research findings supported the utilisation of interactive and visually rich media in the classroom. The integration of Canva can foster students’ motivation, engagement, and the development of writing skills. Students should use Canva for their learning materials, as it is one of the learning facilities provided by the Ministry of Education.